Pelayanan Kesehatan Gratis Untuk Warga Lanjut Usia Di Desa Kurahan - Annisa, Viviane; Henityastama, Milinian Tree Multi; Wibowo, Rizky; Ariansyah, Damas Baik; Febrina, Binta Setya; Nugroho, Arie; Muhammad, Hasman Zhafiri; Rebia, Rina Afiani; Tuti Hidayah; Bella Novita Muktiari (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
This community service activity was carried out in Kurahan Village, Sidoarum Village, Godean District, Sleman Regency, with a focus on the elderly with an age range of 40 to 70 years who are a vulnerable group that often faces various chronic health problems such as diabetes, hypertension, heart disease, mobility disorders, and mental health. Given the importance of access to health for the elderly, who are often constrained by economic, transportation, and information factors, this activity aims to provide accessible and quality health services. This activity involves a medical team consisting of orthopedic specialists, mental health specialists, and pharmacists. This health check service includes consultation, health checks, and the provision of free medicines. The number of participants who participated was 85 participants, consisting of 66 women and 19 men. The results of the activity showed high enthusiasm from the community, where most participants were satisfied or very satisfied with the services provided. This activity not only met the participation target but also succeeded in increasing the awareness of the elderly to be more proactive in maintaining their health. This was evidenced by the commitment of the participants to conduct routine health checks, visit the clinic if sick, follow a healthy lifestyle, and comply with recommendations to take medication regularly.